Phlebotomine salivas inhibit immune inflammation-induced neutrophil migration via an autocrine DC-derived PGE(2)/IL-10 sequential pathway - Carregaro, Vanessa (The Society for Leukocyte Biology, 2008)
In the present study, we investigated whether saliva from Phlebotomus papatasi and Phlebotomus duboscqi inhibited antigen-induced neutrophil migration and the mechanisms involved in these effects. The pretreatment of immunized mice with salivary gland extracts (SGE) of both phlebotomines inhibited OVA challenge-induced neutrophil migration and release of the neutrophil chemotactic mediators, MIP-1α, TNF-α, and leukotriene B(4) (LTB(4)). Furthermore, SGE treatment enhanced the production of anti-inflammatory mediators, IL-10 and PGE(2). SGE treatments failed to inhibit neutrophil migration and MIP-1α and LTB(4) production in IL-10(−/−) mice, also failing in mice treated with nonselective (indomethacin) or selective (rofecoxibe) cyclooxygenase (COX) inhibitors. COX inhibition resulted in diminished SGE-induced IL-10 production, and PGE(2) release triggered by SGE remained increased in IL-10(−/−) mice, suggesting that prostanoids are acting through an IL-10-dependent mechanism. SGE treatments in vivo reduced the OVA-induced lymphoproliferation of spleen-derived cells. Further, the in vitro incubation of bone marrow-derived dendritic cells (DC) with SGE inhibited the proliferation of CD4(+)T cells from OVA-immunized mice, which was reversed by indomethacin and anti-IL-10 antibody treatments. Supporting these results, SGE induced the production of PGE(2) and IL-10 by DC, which were blocked by COX inhibition. These effects were associated with the reduction of DC-membrane expression of MHC-II and CD86 by SGE treatment. Altogether, the results showed that Phlebotomine saliva inhibits immune inflammation-induced neutrophil migration by an autocrine DC sequential production of PGE(2)/IL-10, suggesting that the saliva constituents might be promising therapeutic molecules to target immune inflammatory diseases.